Influence of surgical masks on the avoidance of virtual pedestrians - Bühler, Marco A.; Lynch, Sean D.; Bhojwani, Trineta M.; Zidan, Ahlam; Fiset, Félix; McFadyen, Bradford J.; Lamontagne, Anouk (Frontiers in Virtual Reality, 2023)
To combat the COVID-19 pandemic, governments around the world have proposed a series of mitigation strategies. While responses varied across different governing bodies, recommendations such as social distancing and the use of surgical masks were nearly universal. These recommendations, as well as the social anxiety that emerged during the pandemic, are likely to have influenced pedestrian interactions. In this study, we have examined the effect of surgical masks on locomotor circumvention strategies in response to virtual pedestrians. We further explored the relationship between measures of obstacle clearance and feelings of anxiety related to community ambulation in the context of the pandemic. Using virtual reality, locomotor circumvention strategies in response to approaching pedestrians with and without surgical masks were measured in a sample of 11 healthy young individuals. Additionally, a questionnaire was developed and used to gain insights on participant's behaviours during and after a strict period of restrictions that were in effect before the summer of 2020. Results showed that participants maintained a larger clearance when virtual pedestrians wore a surgical mask. Furthermore, clearance was positively associated with anxiety towards community ambulation in the context of the pandemic. Our findings provide evidence that mask wearing elicits an increase in physical distancing during pedestrian interactions. Furthermore, results indicate that social context and mental health status influence locomotor outcomes measured in the context of a pedestrian interaction task and highlight the potential of virtual reality simulations to study locomotion in the community setting.